An analysis of research hotspots and trends in fashion design based on Chinese cultural elements - Chen, Shuangshuang; Pashkevych, Kalyna (Art and Design, 2026)
Chinese culture, rooted in thousands of years of historical development, demonstrated profound philosophical depth and aesthetic vitality. Its integration into fashion design attracted growing academic attention. The purpose of this study was to systematically analyse the research progress, core themes, and evolving trends in this field. A total of 1,214 academic articles indexed in the China National Knowledge Infrastructure database were examined using CiteSpace software. Bibliometric and visualisation methods were applied to investigate annual publication volume, author and institutional collaboration networks, highly cited literature, keyword co-occurrence, clustering, burst detection, and timeline distribution. It was found that research output increased steadily and peaked in 2024. Collaborative relationships among researchers and institutions remained fragmented, with academic influence concentrated among a small number of prolific contributors and key universities. Highly cited studies primarily addressed the contemporary transformation of traditional motifs, cultural innovation, and design methodology. Keyword clustering identified “New Chinese Style”, “cultural innovation”, “traditional craftsmanship”, and “design expression” as dominant themes. Timeline and burst analyses revealed a trend shift from heritage- oriented exploration to interdisciplinary integration, digital empowerment, and market-oriented innovation. This study offered theoretical insights and methodological references for scholars, educators, and designers engaged in the sustainable and creative application of Chinese cultural elements in fashion. It also contributed to the global dissemination and contemporary reinterpretation of Chinese culture within fashion discourse